Design, analysis and fabricate small cross flow turbine for Sungai Pahang - Mohamad Normazuan, Mustafa (2012)
This thesis is about doing analysis and investigations on river flow rate in Malaysian River which focusing at Sungai Pahang, which is form the investigation the small cross flow are design by consider the data and the characteristic that are collected. Through this analysis and investigation could obtain the potential of running a Water Turbine System (WTS). Demand for electricity around the world increase day by day, and plant that are used nowadays many of that are not renewable energy such as coal power plant, fossil-fuel derived electricity, where the source and supply of this raw material source are decrease day by day and the price are increase, because of this global crisis water turbine system are come out. This innovation are come out to overcome this crisis due to the hydropower that are known as renewable power energy. This project are dedicated to people that leave deep inland can reach and used a electricity especially for this project are dedicated and special for Sungai Pahang river.The main problem statement is on location limitation to obtain peak flow rate of river to running water turbine systems which is depending on depth and width of the river and also from the velocity of sectional area of river. Other than that, choosing most suitable water turbine system is also one of main criteria to be taken in this research. Water Turbine are one of clean renewable energy sources which holding high percentage of energy resource provider among renewable energy. This thesis will carry on with modeling a WTS that can be recommended to construct in Sungai Pahang. The analysis on flow rate of Pahang River are done by calculating potential Power (Watt) that could produced based on volume flow rate data that obtain from Department of Irrigation and Drainage of Malaysia. Since water turbine could provide electricity power without affecting pollution to the environment. Water turbines systems also are cheapest resource to be obtain. Final modeling of water turbine system is completed by Computer Aided Design,CAD software and will be analyzed by using Computational Fluid Dynamic, CFD software.